(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
Contemporary architecture has lost its identity and social purpose, adapting to the capitalist system. This study explores whether the Metaverse, as a virtual city, follows a similar evolution. Nowadays, constructions in the Metaverse focus on economic gain, neglecting social welfare and their essence of functionality, aesthetics, and sustainability. The research examines whether virtual buildings prioritize economic value over artistic value, using one of the first Metaverse worlds: Second Life, as an example. Additionally, it evaluates whether it is worth sacrificing the social purpose of architecture for economic benefits, considering the potential impact on both real and virtual ecosystems.